National Service for Health : the Labour Party's post-war policy (London : Labour Party)
1943-04 1943 1940s 24 pages It is assumed that the aim of the service will be the safety and comfort of the mother and baby ; that all personnel concerned must be fully capable for their job, and should co-operate closely, before, during, and after the confinement; and that all the services should be co-ordinated under the Regional Health Committee. (1) ANTE-NATAL SERVICE There should be ante-natal supervision of all expectant mothers, and, when necessary, treatment. For this purpose, ante-natal clinics are essential and should become an important part of the work of the Local Health Centres. Patients should (as now) be encouraged to attend the clinic, both for medical examination and for advice and help as to preparations for their confinement (such as the early booking of a midwife or hospital bed). The clinics should be staffed from the Maternity Department of the Divisional Hospital. The Dental Service at the Health Centre should be available for the treatment of expectant mothers. Health visitors will also be attached to the Centre, and will be in a position, through their normal visits to patients' homes, to ensure that the advice given to mothers at the clinic is understood and carried out. The health visitor will also be able to advise whether the mother's home conditions are, or can be made, suitable for her confinement, or whether this should take place in hospital. (In general, all first confinements, and all confinements which are likely to show some departure from the normal, should take place in hospital.) If the staff of health visitors is adequate and competent, and if the other services are manifestly of a high standard, the health visitor should be able to allay unnecessary anxiety and to persuade the mothers to make full use of the services offered. (2) CONFINEMENTS (a) Home Cases Every effort must be made to ensure the efficient working of the Midwives Act, 1936, with the direct appointment of qualified and competent midwives by the Local Supervising Authority. This service should be organised from the Health Centre. Sterilised maternity outfits should be available for all mothers. A uniformly good set should be provided and regarded as part of the necessary equipment of the midwife. Ample provision for domestic assistance must be ensured. The Local Authority should have a service of suitable women for employment as "home helps," a regular salary being paid for full-time work. Domestic assistance should be available for special cases during pregnancy, and for a longer period than two weeks after the confinement, whenever necessary. (b) Hospital Cases The hospital provision for maternity cases must be adequate, and must include beds for emergency cases of all kinds. The patients should remain in hospital for not less than the minimum period of 14 days. It is desirable that there should be small wards of not more than four beds. Proper isolation accommodation must be provided, with all precautions against puerperal infection. Whether the confinement is in hospital or in the patient's home, labour should be made as painless as possible ; provision must be made for anaesthesia. In hospital this is easy ; at home, methods which the midwife can use should be developed and taught. 20 36/H24/40